Integration of information systems in management of public and private universities in Kenya : a case of JKUAT and Strathmore University. - Muhiri, Mwangi Edwin (Strathmore University, 2009)
The integration of information systems in the management of universities was determined by analyzing the following : i) A model that determines the alignment of Information systems with the Universities’ business strategy ii) Identifying the indicators for measuring IS/IT Strategic alignment iii) Measuring the relationship of the constructs in the alignment model. Regression analysis supported the contributory relationship of IT governance and IT business alignment on University performance. In the research model University performance was the dependent variable. The standardized co-efficient beta in the coefficient table at Strathmore University revealed that the weights of the independent variables in the regression analysis were 0.34 for IT governance and 0.29 for IT business alignment, implying that IT governance enhances the university performance by almost 34% and IT business alignment contributes 29% of the university performance. Co-efficient analysis at JKUAT revealed the co-efficient of the independent variables in the regression analysis were 0.27 of IT governance and 0.23 for IT business alignment, implying that IT Governance enhances university performance by almost 27% and IT business Alignment contributes 23% to the university’s performance. From the analysis the general observation was IT governance contribution more to university performance with a higher percentage than IT business alignment.
Partial fulfillment for award of the degree of Masters of Science in Information Technology
Keywords: Higher Education -- Automation; University Administration; Information Systems -- Higher Education